The iron empire / 7. - Dashner, James, 1972- (Infinity ring, 2014)
"At long last, Dak, Sera, and Riq travel back in time to the moment it all began. Their mission: to save the life of young Alexander the Great. But they are not the only time travelers in ancient Greece. An epic battle against their most dangerous foe awaits them...and history will be written by the victors"--Back cover.